2021
DOI: 10.3390/jcm10040643
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes of Small for Gestational Age in Twin Pregnancies: Twin vs. Singleton Charts

Abstract: Twin pregnancies are commonly assessed using singleton growth and birth weight reference charts. This practice has led to a significant number of twins labelled as small for gestational age (SGA), causing unnecessary interventions and increased risk of iatrogenic preterm birth. However, the use of twin-specific charts remains controversial. This study aims to assess whether twin-specific estimated fetal weight (EFW) and birth weight (BW) charts are more predictive of adverse outcomes compared to singleton char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
(42 reference statements)
3
18
0
Order By: Relevance
“…Our findings suggest that, compared with singleton charts, twin-specific charts can identify more accurately those infants who are at the highest risk of developing adverse neonatal outcome. This superior accuracy of twin charts has also been demonstrated in previous studies investigating other perinatal outcomes and neonatal mortality 1,21,22 . Our previous study identified that twin-specific charts also outperformed singleton charts in the prediction of abnormal fetal Doppler parameters 21 , suggesting that the twin charts are better at identifying fetal growth restriction and might therefore be expected to correlate better with adverse perinatal outcome.…”
Section: Interpretation Of Study Findings and Comparison With The Pub...supporting
confidence: 68%
See 1 more Smart Citation
“…Our findings suggest that, compared with singleton charts, twin-specific charts can identify more accurately those infants who are at the highest risk of developing adverse neonatal outcome. This superior accuracy of twin charts has also been demonstrated in previous studies investigating other perinatal outcomes and neonatal mortality 1,21,22 . Our previous study identified that twin-specific charts also outperformed singleton charts in the prediction of abnormal fetal Doppler parameters 21 , suggesting that the twin charts are better at identifying fetal growth restriction and might therefore be expected to correlate better with adverse perinatal outcome.…”
Section: Interpretation Of Study Findings and Comparison With The Pub...supporting
confidence: 68%
“…This superior accuracy of twin charts has also been demonstrated in previous studies investigating other perinatal outcomes and neonatal mortality 1,21,22 . Our previous study identified that twin-specific charts also outperformed singleton charts in the prediction of abnormal fetal Doppler parameters 21 , suggesting that the twin charts are better at identifying fetal growth restriction and might therefore be expected to correlate better with adverse perinatal outcome. In this study, we have shown that twin charts are better than singleton charts at identifying twins at increased risk of neonatal morbidity and mortality.…”
Section: Interpretation Of Study Findings and Comparison With The Pub...supporting
confidence: 68%
“…The study concluded that the use of singleton charts was associated with misclassification of a large number of twins as at risk of FGR 31 . Therefore, twin-specific charts could reduce unnecessary medical interventions prenatally and postnatally.…”
Section: Assessment Of Fetal Growthmentioning
confidence: 99%
“…It has been shown that use of these charts does not increase the incidence of stillbirth, but does in fact reduce the number of twins diagnosed as FGR compared to customized singleton charts (7.1% vs 12.8%) 30 . Moreover, a recent study which investigated the risk of perinatal mortality, preterm birth, hypertensive disorders of pregnancy and admission to the neonatal unit in twins according to whether classification as small‐for‐gestational age (SGA) was determined using singleton or twin charts demonstrated that twins classified as SGA according to the singleton charts but not according to the twin charts had similar outcomes to twins classified as appropriate‐for‐gestational age 31 . The study concluded that the use of singleton charts was associated with misclassification of a large number of twins as at risk of FGR 31 .…”
Section: Assessment Of Fetal Growthmentioning
confidence: 99%
See 1 more Smart Citation